2008
DOI: 10.1167/8.12.9
|View full text |Cite
|
Sign up to set email alerts
|

Faces in the cloud: Fourier power spectrum biases ultrarapid face detection

Abstract: Recent results show that humans can respond with a saccadic eye movement toward faces much faster and with less error than toward other objects. What feature information does your visual cortex need to distinguish between different objects so rapidly? In a first step, we replicated the "fast saccadic bias" toward faces. We simultaneously presented one vehicle and one face image with different contrasts and asked our subjects to saccade as fast as possible to the image with higher contrast. This was considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
85
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 51 publications
(55 reference statements)
7
85
0
Order By: Relevance
“…This result is somewhat puzzling given the specificity of the faces to capture attention as described above. Moreover, a fast bias toward faces has been reported recently (Crouzet, Thorpe, & Kirchner, 2007;Honey et al, 2008). In a saccadic choice paradigm, Crouzet et al (2007) showed that early selective saccades could be directed toward faces but not toward other categories (animals and means of transport).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This result is somewhat puzzling given the specificity of the faces to capture attention as described above. Moreover, a fast bias toward faces has been reported recently (Crouzet, Thorpe, & Kirchner, 2007;Honey et al, 2008). In a saccadic choice paradigm, Crouzet et al (2007) showed that early selective saccades could be directed toward faces but not toward other categories (animals and means of transport).…”
Section: Discussionmentioning
confidence: 75%
“…When they replaced the original photographs by scrambled images in which the whole facial configuration was disrupted, the pop-out effect disappeared, leading the authors to conclude that the pop-out effect reflects high-level, holistic parallel processing of faces. Yet, while replicating the original finding by Hershler and Hochstein, VanRullen (2006) reported that impairing the holistic processing by inverting faces had only a minor effect on search performance; he argued that the face popout effect may be explained by low-level differences between faces and other categories, such as the Fourier amplitude spectrum (see also Honey, Kirchner, & VanRullen, 2008). Thus there is still a controversy as to whether the face pop-out effect is driven by low-level visual factors or depends on high-level mechanisms.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Early in visual processing object manifolds are entangled, albeit to lesser extent than at the level of the retina, reflecting the weakness of the formatting of the information for making categorical decisions. Ostensibly some portions of a manifold are less entangled in EVC, possibly because of categorical biases in low-level stimulus features (Honey, Kirchner, & VanRullen, 2008). Exemplars producing activity localized to partially untangled portions of the manifold in EVC would have a subsequent advantage for categorization in IT.…”
Section: Discussionmentioning
confidence: 99%